Milking system and premilking routines have a strong effect on the microbial community in bulk tank milk - Sun, Li; Lundh, Åse; Höjer, Annika; Bernes, Gun; Nilsson, David; Johansson, Monika; Hetta, Mårten; Gustafsson, Anders H.; Hallin Saedén, Karin; Dicksved, Johan (2022)
In this study, we investigated the variation in the microbial community present in bulk tank milk samples and the potential effect of different farm management factors. Bulk tank milk samples were collected repeat-edly over one year from 42 farms located in northern Sweden. Total and thermoresistant bacteria counts and 16S rRNA gene-based amplicon sequencing were used to characterize microbial community composi-tion. The microbial community was in general hetero-geneous both within and between different farms and the community composition in the bulk tank milk was commonly dominated by Pseudomonas, Acinetobacter, Streptococcus, unclassified Peptostreptococcaceae, and Staphylococcus. Principal component analysis including farm factor variables and microbial taxa data revealed that the microbial community in milk was affected by type of milking system. Milk from farms using an au-tomatic (robot) milking system (AMS) and loose hous-ing showed different microbial community composition compared with milk from tiestall farms. A discriminant analysis model revealed that this difference was depen-dent on several microbial taxa. Among farms using an automatic milking system, there were further differ-ences in the microbial community composition depend-ing on the brand of the milking robot used. On tiestall farms, routines for teat preparation and cleaning of the milking equipment affected the microbial community composition in milk. Total bacteria count (TBC) in milk differed between the farm types, and TBC were higher on AMS than tiestall farms (log 4.05 vs. log 3.79 TBC/mL for AMS and tiestalls, respectively). Among tiestall farms, milk from farms using a chemical agent in connection to teat preparation and a more frequent use of acid to clean the milking equipment had lower TBC in milk, than milk from farms using water for teat preparation and a less frequent use of acid to clean the milking equipment (log 3.68 vs. 4.02 TBC/mL). There were no significant differences in the number of thermoresistant bacteria between ...